Application of Solution-Focused Brief Therapy (SFBT) to Help Clients with Anxiety Issues - Rabi’atul Adawiyah Haron; Abu Yazid Abu Bakar; Kadek Suranata (Bisma The Journal of Counseling, 2020)
The counseling services were created to help people deal with life's problems in more effective ways. Various theories and approaches have been introduced so that practitioners are more confident and have directions in carrying out their duties. Solution-Focused Brief Therapy (SFBT) is one the approaches that views individuals have inner strengths and can deal with the problems they are facing in their daily lives. Feeling anxious is everyone's normal emotion. However, for some people, this anxiety can disrupt their life. This concept paper examines whether the Solution-Focused Brief Therapy (SFBT) is suitable to be applied for clients who suffer from anxiety issues in life.